2008
DOI: 10.1186/1749-7922-3-9
|View full text |Cite
|
Sign up to set email alerts
|

Acute gallbladder torsion: an unexpected intraoperative finding

Abstract: Gallbladder torsion is an uncommon clinical entity and a difficult condition to diagnose preoperatively. Since its first description in 1898 by Wendel there have been over 500 documented cases in the literature. It is known to occur when there is rotation of the gallbladder along the axis of the cystic duct and vascular pedicle. Except for isolated cases reported in childhood, this disease is more frequently encountered in the elderly with 85% of the cases reported between the ages of 60 and 80 years. There is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
84
0
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(92 citation statements)
references
References 8 publications
1
84
0
7
Order By: Relevance
“…16 Thus, early diagnosis and early intervention can reduce mortality associated with this condition. 16,17 Ultrasonography and computed tomography are nonspecific investigations for diagnosis of volvulus. 15 A hepatobiliary iminodiacetic acid (HIDA) scan theoretically shows a characteristic, though not sensitive, "bulls eyes" appearance of the torsed gall bladder.…”
Section: Discussionmentioning
confidence: 99%
“…16 Thus, early diagnosis and early intervention can reduce mortality associated with this condition. 16,17 Ultrasonography and computed tomography are nonspecific investigations for diagnosis of volvulus. 15 A hepatobiliary iminodiacetic acid (HIDA) scan theoretically shows a characteristic, though not sensitive, "bulls eyes" appearance of the torsed gall bladder.…”
Section: Discussionmentioning
confidence: 99%
“…Torsion of gall bladder has mortality rate of 6% though no death occurred in patients diagnosed preoperatively [16]. Thus, early diagnosis and early intervention can reduce mortality associated with this condition [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10] The clinical incidence of GV has been reported as 1 in 365,520 hospital admissions. 11 Multiple authors have postulated reasons for torsion of the gallbladder. Boonstra suggested that GV only occurs in the absence of gallbladder fixation to the liver.…”
Section: Illustrative Casementioning
confidence: 99%
“…12 The term visceroptosis, referring to relaxation and atrophy of a previously normal mesentery in the elderly, has been used to describe this condition of mesenteric elongation and thinning, which is necessary for GV to occur. 11,[13][14][15][16][17] Atherosclerosis of the cystic artery and a tortuous cystic duct are also hypothesized as cofactors, as they may serve as fulcrums for gallbladder torsion. 3,17 Other investigators have noted coexisting conditions that may predispose to GV.…”
Section: Illustrative Casementioning
confidence: 99%